The development and effectiveness of a standard education programme to prevent tuberculosis for public healthcare workers in Malaysia / Sivarajan Ramasamy - Sivarajan, Ramasamy (2018)
Tuberculosis (TB) is a major occupational hazard for healthcare workers (HCWs) worldwide. The main objective of this study is to develop and evaluate the effectiveness of standard education programme to prevent Tuberculosis for public healthcare workers in Malaysia. The health belief model was applied as the main theoretical framework in this study to understand the perception of risk, perception of threat, perception of benefit and cues of action of HCWs on TB disease and prevention. The study duration for cross sectional study took 8 months to complete (January 2016 to August 2016) meanwhile the intervention study was done concurrently, and it took six months (February 2016 to July 2016) to complete the intervention study. First, a cross-sectional study was conducted within 11 states in Malaysia. This study evaluated the association between occupation and knowledge, attitude, and practice (KAP) on TB prevention among HCWs in Malaysia the sample population (n = 3,344) consisted of doctors, nurses, medical assistants, and health attendants. Based on job status, doctors had a positive correlation with KAP, as 68% of doctors had the high knowledge and 69% had good practice; however, the majority of doctors scored in the neutral attitude category. Similarly, there was a strong positive correlation between knowledge and practice among nurses. Nurses demonstrated the highest percentage of good practice compared with other job statuses. Further, the majority of health attendants indicated moderate knowledge with neutral and negative attitudes (90%) and fair and poor practice (33%).Secondly, an educational intervention, STEP, was developed to increase the level of KAP among HCWs on TB disease and prevention. The content and suitability of the STEP programme was validated the by three panel of experts. Thirdly, an intervention study was conducted and STEP programme was delivered based on a participant-centred approach that integrated demonstrations to iv evaluate the effectiveness of the STEP programme. Total of 600 nurses from Kedah state participated in this study and participants were randomised into intervention and control group based on block randomisation. The characteristics of both group were similar at baseline. Pre-test and post-test was performed at immediate, one-month and three-months after the course. Results of this study indicated that baseline knowledge of TB is similar in both intervention and control group. Post STEP programme, there was a significant increase in knowledge,attitude and practice mean scores in the intervention group. The result showed that the effect of STEP at post-intervention are improvement of score in knowledge, attitude and practice with 10.43, 9.26 and 1.78 scores. Meanwhile, the effect of STEP in high knowledge, positive attitude and good practice showed significant improvement with odds ratio of 2199.8 ,77.8 and 1.07 respectively in intervention group. The findings showed immediate improvement noted on knowledge and attitude and significant improvement on practice only noted at three months post-intervention. In conclusion, Standard Tuberculosis Education Program (STEP) is effective in improving KAP on TB prevention among HCWs in Malaysia and STEP should be incorporated in current guideline and implemented as a standard health education training programme for HCWs in Malaysia.